ChaletPS - Ibrahim Shalhoub; Moayad Abu Zaroor (My University, 2023)
We noticed that many people face difficulty when booking a chalet, whether it is because they do not know the names of the chalets and the difficulty of searching for them or the difficulty of communicating as they need to communicate with the owner to know the empty reservations. Therefore, we will make a website and application that makes it easier for the user to know the many chalets and the dates available to book the chalet without the need to communicate directly with the owner and know the road to the chalet through the GPS in addition to the possibility of communicating online with the owner and do not forget that it is easy for the chalet owner to advertise his chalet on the site and not only limited to advertising on social media. This project makes it easier for people who want to book a chalet to know the dates of the empty reservations and saves them a lot of time in searching for a chalet on social networking sites and knowing the prices instead of communicating directly with the owners of the chalets in addition to knowing the location of the chalet on the map. At first, the user is logged in, whether he is a regular user or the owner of a chalet, to show a page with many shared chalets on the site, when he clicks on the name of the chalet, a page appears with the details of the specifications mentioned previously, the price and the available days, and when the reservation is made, the admin is notified that the reservation has been made On a certain date, and if the reservation is confirmed, the reservation appears on the user’s reservations list and a number appears to contact the person who will carry out the delivery process, and in the end the user rate the chalet.